Voting Choice - Malenko, Andrey; Malenko, Nadya (Review of Financial Studies, 2026)
Abstract Traditionally, fund managers cast votes on behalf of fund investors. Recently, there is a shift toward “pass-through voting,” with funds offering investors a choice: delegate votes to the fund or vote themselves. We develop a framework to study the implications of voting choice. While it helps reflect heterogeneous investor preferences, it also shapes the informational content of the vote, and these forces can conflict. When interests are aligned, voting choice improves information aggregation and investor welfare. With preference heterogeneity or costly information, however, it can make investors worse off by weakening informed. (JEL D72, D82, D83, G34, K22)